Marketing Mix-7P dan Religi Terhadap Keputusan Menjadi Nasabah (Survey Pada PT. Bank BRISyariah KCP Wahid Hasyim Jombang) - Sa’adah, Haqiqotus; Sopingi, Imam (MALIA: Journal of Islamic Banking and Finance, 2019)
This study aims to test how far the decision to become a customer or customer interest in sharia banking, especially PT. Bank BRISyariah KCP Wahid Hasyim Jombang by observing customer’s behaviors. There are seven factors that influence the decision to become a customer, they are product, price, place, promotion, people, process, and physical evidance called marketing mix-7p and one special factor ini this case is religion. Religious factor in this study is the image of sharia.The results showed that marketing mix-7p variables (X1) and religion variables (X2), had a positive influence. The regression equation Y = -5.792 + 0.234 + 0.644. The F test (simultaneous) showed that the marketing mix-7p variables and religion variables both had significant influences on the decision to be a customer with a significance level of 0.000 or 0%. But based on T test (partial), marketing mix-7p variables significantly influence the decision to become a customer of 0,000, while religious variables significantly influence the decision to become a client of 0.001. The contribution of marketing mix-7p and religion variables to the decisions to become customers is shown by the coefficient of determination that has been equaled 0.783 means that the marketing mix-7p and religion influence the decision to become a customer of 78.3% while sisahnya by 22% influenced by other variables outside the model Used by researchers.And the result of this research get R = 0,885 show R almost close to number 1, meaning between marketing mix-7p and religion variable to decision become customer have influence.